2015
DOI: 10.1186/s40608-015-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity, physical activity and sugar-sweetened beverage consumption in adolescents of Pacific islands: results from the Global School-Based Student Health Survey and the Youth Risk Behavior Surveillance System

Abstract: BackgroundOverweight, obesity and their consequences are challenges to sustainable social and economic development in Pacific island countries and territories (PICTs). Complementing previous analyses for adults, the purpose of this paper is to synthesise available data on overweight, obesity and their risk factors in adolescents in the region. The resulting Pacific perspective for the younger generation will inform both the national and regional public health response to the crisis of noncommunicable diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 26 publications
1
50
1
1
Order By: Relevance
“…Conversely, Asian populations have higher abdominal adiposity than European populations for the same BMI , a finding that prompted the World Health Organization (WHO) to propose specific thresholds (23 and 25) to detect overweight and obesity in these populations . As already observed in other countries in the Pacific area , the prevalence of overweight is high in New Caledonian adults and adolescents , but differs with the BMI‐based reference used . To our knowledge, these BMI‐based indicators have never been compared.…”
Section: Introductionmentioning
confidence: 82%
“…Conversely, Asian populations have higher abdominal adiposity than European populations for the same BMI , a finding that prompted the World Health Organization (WHO) to propose specific thresholds (23 and 25) to detect overweight and obesity in these populations . As already observed in other countries in the Pacific area , the prevalence of overweight is high in New Caledonian adults and adolescents , but differs with the BMI‐based reference used . To our knowledge, these BMI‐based indicators have never been compared.…”
Section: Introductionmentioning
confidence: 82%
“…Indeed, a recent study examining SSB consumption and obesity among adolescents in Pacific island countries and territories found that 37% of students aged 13-15 years reported that they consumed at least one carbonated soft drink per day over the past 30 days (Kessaram et al 2015). …”
Section: Sugar Consumption Per Capita In Selected Countriesmentioning
confidence: 99%
“…Показано, что преимущественно студенты ведут си-дячий образ жизни, много времени проводят за ком-пьютером, мало внимания уделяют дополнитель-ным занятиям физической культурой и спортом [24,25].…”
Section: связь мотивации пищевого поведения и изучаемых параметровunclassified